A brachyopid temnospondyl from the lower Cynognathus Assemblage Zone In the northern Karoo Basin, South Africa - Damiani, Ross J.; Jeannot, Ashleigh M. (Bernard Price Institute for Palaeontological Research, 2002)
A new brachyopid temnospondyl is described from the Early to Middle Triassic Cynognathus Assemblage Zone of the upper Beaufort Group, Karoo Basin of South Africa. It is the fourth named brachyopid from the Karoo and the first from the northern part of the basin. Despite the incomplete nature of the holotype skull, the new brachyopid apparently shows closest affinities to Batrachosuchus watsoni. However, differences in the width of the sensory sulci, the absence of a transverse occipital sulcus, and the presence of a unique narial morphology, warrants separation at the species level. The holotype skull also provides insight into the morphology of the ventral surface of the skull roof and the configuration of the bones between the orbit and the nostril. A referred right mandibular ramus, the most complete yet recovered of a brachyopid, also shows several unique features. A reconsideration of the taxonomy of the brachyopid genus Batrachosuchus reveals that Batrachosuchus watsoni possesses several characters distinct from the type species, Batrachosuchus browni, and is thus transferred to a new genus. In addition, 'Batrachosuchus' henwoodi and Batrachosuchus concordi probably do not pertain to the genus Batrachosuchus. Brachyopid diversity in the Karoo is exceeded only by the Mastodonsauridae and Rhinesuchidae, and they may eventually prove to be important aids in the biostratigraphy of the Cynognathus Assemblage Zone.
Main article
Keywords: temnospondyl; Cynognathus; Karoo